Facts about Wildlife Diseases: Ehrlichiosis - Yasmin Tavares; Samantha M. Wisely (EDIS, 2020)
Ehrlichiosis is a bacterial disease that is transmitted to humans and animals from ticks. In most cases, symptoms are mild, but sometimes if antibiotic treatment is delayed, it can cause severe illness and even death. In Florida, ehrlichiosis is an emerging disease. The hotspot of transmission is in north central Florida, but the disease is underdiagnosed. This 4-page fact sheet written by Yasmin Tavares and Samantha Wisely and published by the UF/IFAS Department of Wildlife Ecology and Conservation describes ehrlichiosis and explains how it is transmitted, how to know if you have it, and how to prevent yourself and your friends and family from getting it.